First Cryo-Scanning Electron Microscopy Images and X-Ray Microanalyses of Mucoromycotinian Fine Root Endophytes in Vascular Plants - Albornoz, Felipe E.; Hayes, Patrick E.; Orchard, Suzanne; Clode, Peta L.; Nazeri, Nazanin K.; Standish, Rachel J.; Bending, Gary D.; Hilton, Sally; Ryan, Megan H. (Frontiers in Microbiology, 2020)
Aims. Arbuscule-producing fine root endophytes (FRE) (previously incorrectly Glomus tenue) were recently placed within subphylum Mucoromycotina; the first report of arbuscules outside subphylum Glomeromycotina. Here, we aimed to estimate nutrient concentrations in plant and fungal structures of FRE and to test the utility of cryo-scanning electron microscopy (cryoSEM) for studying these fungi. Methods. To do so, we used replicated cryoSEM and X-ray microanalysis of heavily colonized roots of Trifolium subterraneum. Results. Intercellular hyphae and hyphae in developed arbuscules were consistently very thin; 1.35 ± 0.03 µm and 0.99 ± 0.03 µm in diameter, respectively (mean ± SE). Several intercellular hyphae were often adjacent to each other forming ‘hyphal ropes’. Developed arbuscules showed higher phosphorus concentrations than senesced arbuscules and non-colonized structures. Senesced arbuscules showed greatly elevated concentrations of calcium and magnesium. Conclusions. While uniformly thin hyphae and hyphal ropes are distinct features of FRE, the morphology of fully developed arbuscules, elevated phosphorus in fungal structures, and accumulation of calcium with loss of structural integrity in senesced arbuscules are similar to glomeromycotinian fungi. Thus, we provide evidence that FRE may respond to similar host-plant signals or that the host plant may employ a similar mechanism of association with FRE and AMF.